Pengaruh Kualitas Pelayanan Terhadap Kepuasan Peserta Bpjs Ketenagakerjaan Cabang Meulaboh Selama Pandemi - Vika Lusiana Sari (Cattleya Darmaya Fortuna, 2021)
Consumer satisfaction is the most important main thing to be considered by business people or businesses in order to maintain a sense of trust and consumer comfort. The government issues various policies, such as social distancing, work from home, and invites people to stay at home. Restrictions on activities carried out by BPJS Ketenagakerjaan branch meulaboh by using online services in the form of LAPAK ASIK (service without physical contact) to reduce the spread of covid-19 to participants. The satisfaction of participants can be considered by the quality of service provided, the quality of service that meets the expectations of participants becomes important. This research aims to find out the effect of service quality on the satisfaction of participants BPJS Ketenagakerjaan Meulaboh Branch. Service quality variables consist of Tangible Indicators, Empathy, Reliability, Responsiveness, and Assurance. The type of research used is a type of quantitative descriptive research and the sample used amounted to 20 respondents. Data collection techniques using questionnaires using google from. Data analysis uses multiple linear regressions. The results showed that the service quality variable was declared to affect the satisfaction of participants BPJS Ketenagakerjaan Meulaboh Branch simultaneously. Independent variables are able to explain the relationship and its effect on dependent variables by 87.7%. There was a partially significant influence on service quality variables on customer satisfaction with a significance yield of t(0.000) < α 0.005.